X-ray microtomography with monochromatic synchrotron radiation for evaluation of the penetration depth of nanosilver solution in tooth dentin (LLC "Endo Press", 2020)
The results of measuring the depth of penetration of the ultrasonicated bactericidal solution of nanosilver Poviargrol into Dentinal Tubules of the tooth are presented. Investigations were carried out using the method of monochromatic X-ray microtomography with synchrotron radiation source with a critical energy of 7.1 keV. The diffusion indices indicate a deeper penetration of the ultrasonic-activated solution of nanosilver into the dentin in comparison with free penetration. Monochromatic X-ray microtomography with synchrotron radiation source can be an effective method of analyzing the penetration of inorganic drugs into hard tooth tissues.